Incidence and outcome of thyroglossal duct cyst - A. H. M. Delwar1; Jahangir A. Mazumder; M. S. Rashid; M. G. Mustafa; A. B. M. Tofazzal Hossain (2020)
Background: Thyroglossal duct cyst (TGDC) is the cyst in the cervical midline that arises from the embryonic remnant of the thryroglossal duct. It is most common congenital abnormality in the head and neck region which may present at any age particularly occur in children. The definitive treatment is surgical excision of the cyst and tract. Methods: It is a cohort retrospective study of 26 cases in the Department of Otorhinolaryngology and Head-Neck surgery, Comilla Medical College Hospital, Bangladesh from 01 July 2016 to 31 June 2019. Results: Incidence of TGDC was 0.02% out of total outdoor patient and 0.94% in total indoor routine operation. All patient was operated by Sistrunk’s procedure and recurrent 2 (7.69%) cases were operated by modified or extended Sistrunk’s procedure without complications afterwards. Of them female was 14 (53.85%), male was 12 (46.15%), children were 22 (84.61%), adult were 4 (15.35%). Infrahyoid was 21 (80.76%), surahyoid was 5 (19.24%). The patient presented as painful abscess were 10 (38.46%) and fistula were 3(11.51%), painless cyst was 8 (30.77%) and fistula were 5 (19.24%). Conclusions: TGDC is common congenital anomaly. It has a various type of presenting feature. Sistrunk’s procedure is gold standard surgical treatment procedure. But recurrence cases need modified or extended Sistrunk’s procedure to minimize the postoperative complication and manage the patient’s hope and requirements.